(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of research to know academic information system, determine the effect of the application of academic information systems on quality of academic services, and find great academic information system variables influence the quality of academic services at the State Islamic University Imam Bonjol Padang. Method of this research use combination of quantitative method and qualitative method. Further processing of the results of the questionnaire assessed by interview. The questioner was examined by reliability test, validity test, regression test, a test of determination, and test hypotheses. Processing techniques and data analysis performed using SPSS 26. Survey results revealed that the academic information systems at the State Islamic University Imam Bonjol Padang is a web-based system that can be accessed through the counter and online faculty. This system facilitates student access to academic information, and as a means of gathering information through the rapid academic. The result of data processing and analysis of questionnaires indicates thats the variable academic information system variables significantly influence the quality of academic services at the State Islamic University Imam Bonjol Padang. From the results of data processing and analysis of questionnaires showed that academic information system variables have significant effect the quality of academic services at the State Islamic University Imam Bonjol Padang. It can be seen from the T test, with comparing the t-table and t-result with a= 5%. The result is significant effect of academic information systems with a significant impact on the quality of academic services, with a t-count (3.833) is greater than t-table (1.669). This means that if the academic information system is better, academic service quality will increase.